Representation of Critical Thinking Skills in EFL Algerian Syllabus: The Case of “New Prospects”, Third Year Secondary School Textbook - GASMI, Aoutaf; DIB, Mohamed (Social Sciences Journal, 2023)
Few decades ago, the concept of critical thinking was featured in taxonomies which is a complex process that requires higher level of cognitive skills in the processing of information. This study responds to the idea of critical thinking, English Language Teaching (ELT) and Algerian students by investigating critical thinking in “New Prospects”, the Algerian English language textbook intended for third year secondary school students. The study poses two research questions: (1) To what extent does “New Prospects” help fostering Critical Thinking Skills (CTS) among second year secondary school students? (2) What are the English language teachers’ attitudes and perceptions towards the manifestation of critical thinking skills in “New Prospects”? To answer these questions, the study adopts a content analysis methodology focused on text-based questions and the interview as a tool for participating teachers. The interview is conducted mainly to investigate whether the tasks and questions within “New Prospects” make students think. The study took place in four secondary schools in Laghouat, Algeria. Participants of the study were secondary school teachers of English. This study shows that the Algerian English as a Foreign Language (EFL) textbook, “New Prospects”, contains more textually-explicit questions than questions that promote critical thinking. The present study makes some noteworthy contributions to the current literature